Pattern and features of menstruation among adolescent girls in Haldwani: a cross-sectional study - Goyal, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Menstruation becomes an important aspect in life of an adolescent girl once she attains puberty and is often associated with variable characteristics. Being a development process and a reported significant source of morbidity too, it becomes important to study its pattern and characteristics. The purpose of this study was to determine the pattern of menstruation among adolescent girls. Methods: A cross sectional study was conducted among 574 adolescent girls of 10-19 years age of 6th to 12th grades in four selected government and private schools of Haldwani. Data was collected using a predesigned semi-structured questionnaire with brief interview and examination. Analysis of data was done with help of SPSS version 21. Results: Mean age of the girls was 14.95±1.41 years. Mean age at menarche was 12.94±1.01 years. Majority of girls 441 (76.82%) had cycle length of 21-35 days and it was found that 95 (16.55%) girls had irregular menstrual periods. Rural and urban differences in regularity of menstruation were statistically significant. Duration of flow in majority 300 (52.26%) of girls was 2-4 days followed by 5-7 days in 222 (38.68%). Dysmenorrhoea was reported by 422 (73.52%) of adolescent girls and of them 259 (61.37%) have never used analgesics while 66 (15.63%) have always used analgesics. Girls with absence of pallor were 1.2 (0.8-1.9) times more likely to have regular menstruation as compared to those showing pallor. Conclusions: Irregular menstruation was common among girls and significant association was found with place of residence. Dysmenorrhoea was present in three-fourth of adolescent girls still majority of them have never used analgesics. Daily routine was affected in more than 80% of girls during menstruation.